Reading territory : Indigenous and Black freedom, removal, and the nineteenth-century state - Walkiewicz, Kathryn, 1981- (The University of North Carolina Press, 2023)
"In her newest book Reading Territory, Kathryn Walkiewicz uses literary and historical methods to investigate how the borders of the US settler nation-state shifted throughout the long nineteenth century. She theorizes the roles of federalism and statehood in the production of US empire, particularly during nineteenth-century statehood movements. In the course of following these movements over time, from Georgia (1788) to Florida (1845), Kansas (1861), and Oklahoma (1907), Walkiewicz places Indigeneity and Blackness into a conversation with the rhetorics of states' rights in America. Throughout, she offers careful and nuanced readings of Indigenous and Black agency, conflict, alliance, and contestation as they relate to, and against, statist ideologies of white supremacy. Walkiewicz offers a nuanced, well-researched, and compellingly argued analysis of the ways that Indigenous and Black subjectivities have grappled with these complex relations between statehood and personhood as they sit within the context of an expanding American empire across the nineteenth century"--